PENGARUH PENGARUH MODAL, TENAGA KERJA DAN PRODUKSI TERHADAP PENDAPATAN PETANI RUMPUT LAUT DI DESA PED KECAMATAN NUSA PENIDA - Sari, Rizki Retno; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 11. Nopember 2017(pp.2103-2351), 2017)
This study aimed to analyze influence of capital and labor to the production and income of seaweed farmers in the village of Ped District of Nusa Penida. Data collection and analysis of data through questionnaires. The data used is primary data. The analytical method used, the analysis lane or path analysis to determine the effect of direct and Sobel test is used to determine the effect of indirectly. The analysis showed that capital and labor directly influence the production of seaweed in the village of Ped District of Nusa Penida. In the next test, varaibel capital, labor and production have a direct effect on the income of seaweed farmers in the village of Ped District of Nusa Penida. Variable production of an intervening variable indirect effect on capital and labor income seaweed farmers in the village of Ped District of Nusa Penida.